Islamic Education of Civil Society in the Perspective of Sociology - Purwadhi, Purwadhi; Komara, Endang (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research aims to explore the role of Islamic religious education in shaping civil society through the perspective of religious sociology. Islamic religious education aims to make humans the caliph on earth and integrate religious teachings with the social system that prevails in society. This study uses a qualitative descriptive method with a literature approach, and data analysis is carried out using the content analysis method. The study results show that Islamic religious education facilitates understanding social concepts because Islam has a social purpose. In addition, the sociological approach plays an important role in understanding the meanings of the Qur'an as it relates to social life. Sociology, from the perspective of religion, is a view of life that is considered important in people's lives and has a close relationship with each other. Religion also plays a role in shaping the social structure of society. In the study of the sociology of religion, the focus is on social phenomena in religious societies, not only on religious teachings themselves. This study concludes that Islamic religious education is important in shaping the character of a civilized and common welfare-oriented society. For further research, it is recommended to conduct an empirical study on implementing Islamic religious education in a multicultural society and its impact on social harmony.